Theoretical study on the design of allosteric inhibitors of diabetes associated protein PTP1B - Zhan, Jiuyu; Liu, Zhenyang; Gao, Hongwei (Frontiers in Pharmacology, 2024)
ABSTRACT： The protein tyrosine phosphatase 1B (PTP1B) is a critical therapeutic target for type 2 diabetes mellitus (T2DM). Many PTP1B inhibitors have been reported, however, most of them lack high specificity and have adverse effects.Designing effective PTP1B inhibitors requires understanding the molecular mechanism of action between inhibitors and PTP1B. To this end, molecular dynamics (MD) simulations and molecular mechanics Poisson Boltzmann Surface Area (MM-PB/SA) methods were used to observe the binding patterns of compounds with similar pentacyclic triterpene parent ring structures but different inhibition abilities.Through structure and energy analysis, we found that the positions of cavities and substituents significantly affect combining capacity. Besides, we constructed a series of potential inhibitor molecules using LUDI and rational drug design methods. The ADMET module of Discovery Studio 2020 was used to predict the properties of these inhibitor molecules. Lastly, we obtained compounds with low toxicity and significant inhibitory activity. The study will contribute to the treatment of T2DM.